Low-invasive treatment of fresh injuries in the acromioclavicular joint - Golovakha, Maksim; Shishka, Igor; Banit, Oleg; Babich, Yuriy; Tverdovsky, Anatoliy; Zabielin, Ivan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
Results of treatment of 16 patients with fresh injuries of ligaments in the acromioclavicular joint are presented. The type of injury was classified according to Rockwood. In cases of injury types I-II, conservative treatment was used. In conditions of dislocation types III and V of the above classification, surgical treatment was used. A modified MINAR technique was the method of choice, where either anchor fixation devices with nonabsorbable sutures or AKK-Takelazh systems with high-strength nonabsorbable material were used. The results showed that the use of the above technique for restoration of the acromioclavicular joint made it possible to decrease traumatism of the operation, shorten terms of immobilization, receive positive remote results and restore the full range of movement in the acromioclavicular joint.